DEPRESIASI RUPIAH TERHADAP DOLAR AS DAN PENGARUHNYA TERHADAP EKSPOR DAN IMPOR - Juli Panglima Saragih (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
The depreciation of rupiah against US dollar will make positive and negative implications on the economy of Indonesia. This is a consequence of the open economy system and embraced free foreign exchange system. This paper aims to discuss and analize some implications of the depreciation of Indonesian rupiah upon foreign trade, foreign loans, and government reserve money. This paper uses a qualitative approach with a descriptive-analysis method supported with relevant data and references to the above topic discussed. It was concluded that condition of high depreciation of the rupiah in-mid and long-term should have to encourage surplus of foreign trade balance and decreasing import. This is a constraint on condition of rupiah’s depreciation. Moreover, depreciation of rupiah will be a benefit in competing similar products traded in international market. Depreciation of rupiah also can increase foreign direct investment to finance overall of businesses, as well as finance for development.